The relationship between positive end expiratory pressure and cardiac index in patients with acute respiratory distress syndrome - Fares, Wassim H (2013)
PURPOSE: To evaluate the association between positive end-expiratory pressure (PEEP) and cardiac index in patients with acute respiratory distress syndrome (ARDS). METHODS: This is a secondary cross-sectional analysis of the FACTT multi-center randomized controlled trial enrolling adult patients within 48 hours of ARDS onset. Patients randomized to the pulmonary artery catheter arm, who had PEEP and cardiac index measurements performed within a short period of each other during the first 3 days of the FACTT study enrollment were included in this study. Since FACTT had a 2×2 factorial design, half of the patients were in a ‘liberal fluids’ study arm, and the other half were in a ‘conservative fluids’ study arm. RESULTS: The final study population (833 measurements or observations, in 367 patients) was comparable to the original overall FACTT study population. The mean PEEP level used was 8.2 ± 3.4 cm H(2)O, and the mean cardiac index was 4.2 ± 1.2 liters/minute/m(2). There was no association between PEEP and cardiac index in patients with ARDS, even when adjusted for APACHE score, age, fluid study arm in FACTT, and sepsis. CONCLUSION: In patients with ARDS who are managed with liberal or conservative fluid management protocols, PEEP is not associated with lower cardiac index.